La forza trasformativa delle utopie quotidiane. Un’introduzione - Ilenya Camozzi (Cambio)
The rapidity of recent social transformations and the suspension of much of the knowledge that has settled in our daily lives call for a twofold action: designing new political objectives of social justice and shedding light on analytical tools capable of both laying bare inequalities and the power structures that feed them, and outlining paths of transformative intervention. The link between sociology and utopia emerges here with particular clarity. Both, in fact, refer to an imaginary reconstruction of society. Starting with the most recent thematisation of utopia – whose real, everyday, concrete, embodied character is emphasised – this essay explores the link between utopias, common sense and everyday life. The aim is to weave the threads between the transformations of common sense and everyday utopian practices against the backdrop of that re-enchantment of the everyday of Weberian memory. The space-time of the everyday becomes the stage where minute, banal and taken for granted routines can become counter-hegemonic actions, everyday utopias endowed with transformative power.